A randomised controlled trial of an intervention to promote early presentation of breast cancer in older women: effect on breast cancer awareness. - Linsell, L; Forbes, L; Kapari, M; Burgess, C; Omar, L; Tucker, L; Ramirez, A (2009)
BACKGROUND: There is virtually no evidence for the effectiveness of interventions to promote early presentation in breast cancer. We aimed to test the efficacy of an intervention to equip older women with the knowledge, skills, confidence and motivation to detect symptoms and seek help promptly, with the aim of promoting early presentation with breast cancer symptoms. METHODS: We randomised 867 women aged 67-70 years attending for their final routine appointment on the UK NHS Breast Screening Programme to receive: a scripted 10-min interaction with a radiographer plus a booklet, a booklet alone or usual care. The primary outcome was whether or not a woman was breast cancer aware based on knowledge of breast cancer symptoms and age-related risk, and reported breast checking. RESULTS: At 1 month, the intervention increased the proportion who were breast cancer aware compared with usual care (interaction arm: 32.8% vs 4.1%; odds ratio (OR): 24.0, 95% confidence interval (CI): 7.7-73.7; booklet arm: 12.7% vs 4.1%; OR: 4.4, 95% CI: 1.6-12.0). At 1 year, the effects of the interaction plus booklet, and the booklet, on breast cancer awareness were largely sustained, although the interaction plus booklet remained much more effective. CONCLUSIONS: An intervention to equip older women with the knowledge, skills, confidence and motivation to detect breast cancer symptoms and seek help promptly increases breast cancer awareness at 1 year. Future research will evaluate whether the intervention promotes early presentation and reduces breast cancer mortality.